Study on nitrogen pores, microstructure, and mechanical properties of nickel-free high-nitrogen stainless steel fabricated via LDED regulated by heat input - Chaojing Yu; Dabin Zhang; Zuguo Liu; Dongsheng Wu; Yinliang Zhong; Jiazhu Wu (Virtual and Physical Prototyping)
The most significant challenges in the laser additive manufacturing of high-nitrogen steel are nitrogen loss and nitrogen pores, which significantly impact the microstructure and mechanical properties of the fabricated parts. In this paper, the regulation mechanisms of nitrogen loss, nitrogen pores, microstructure, and mechanical properties in the laser-directed energy deposition of nickel-free high-nitrogen stainless steel were systematically investigated. The results indicate that nitrogen loss gradually increases, and the porosity of the deposited samples first increases and then decreases with the increase in heat input. These changes are the result of the combined effects of the temperature, lifetime, solidification rate, and Marangoni flow of the melt pool. The microstructure of the deposited samples is primarily composed of austenite and ferrite phases. The deposited samples exhibit the highest mechanical properties at a moderate heat input of 80 J/mm. Furthermore, the contribution of solid-solution strengthening, grain-boundary strengthening, and dislocation strengthening to the strength of the deposited samples is discussed.